B1.4 Development of a robust and reliable pulse oximeter for use by frontline healthcare providers caring for children with pneumonia in low-income countries. (4th October 2017) - Boyd, N; Walker, I; King, C; Zadutsa, B; McCollum, E; Bernstein, M; Wilson, I
Abstract : Background: Pneumonia is the leading infectious cause of death in children under five years, with most deaths occurring in low-income countries. Severe pneumonia is associated with hypoxaemia which can be detected using a pulse oximeter. Single-use adhesive oximeter probes common in the UK are not affordable or practical for low-income countries. Led by the charity Lifebox and funded by The Gates Foundation, this 18 month collaborative project between GOSH, UCL and centres in Malawi and Bangladesh, had the aim of designing and testing a modified rechargeable pulse oximeter with a reusable oximetry probe designed specifically for children under five. Methods: We designed a mixed-methods, iterative study to test the usability of the new oximeter and probe in 3 sites, with the primary outcome being time to obtain a reading. Experienced nursing staff at GOSH were asked to test the new device on children in four age categories and provide structured feedback. Results: Across all sites, a measurement was possible in 95% of patients within 5 min and 70% within 1 min. The probe was well tolerated. No difference in time to reading was found between expert users and healthcare workers or between high and low resource settings. It took significantly longer to obtain a reading in neonates and infants than older children. It was significantly more likely to record a reading in under 1 min if the child was calm. Nurses at GOSH provided more appropriate saturation readings than healthcare workers in low resource settings. (Full evaluation of qualitative data ongoing) Conclusion: Our study demonstrates this newly designed, reusable probe is suitable for use in children under 5 years across a range of settings. We identified children under 1 year old and unsettled children as the most challenging groups and highlight the importance of training when interpreting a pulse oximetry reading.